Circular RNA ERBIN Promotes Proliferation of Hepatocellular Carcinoma via the miR-1263/CDK6 Axis - Yang, Shikun; Yu, Fei; Ji, Yang; Shen, Yanjun; Lu, Hao; Gao, Yuan; Zhang, Feng; Wang, Xuehao; Zhang, Chuanyong (Frontiers in Oncology, 2022)
Objectives Hepatocellular carcinoma (HCC) is the most common primary liver cancer and characterized by high aggressiveness and extremely poor prognosis. Increasing evidence has suggested that circular RNAs (circRNAs), which are highly stable, play crucial roles in the progression of multiple malignancies. However, the roles of circRNAs in HCC remain elusive. Materials and Methods The expression patterns of circRNAs in HCC were identified by qRT-PCR. A series of functional experiments both in vivo and in vitro were used to determine the role of circERBIN in HCC proliferation. Bioinformatics and an RNA pulldown assay were used to identify potential downstream targets of circERBIN. Results The expression of circERBIN was upregulated in HCC cell lines and tissues, which was predictive of a poor prognosis in HCC patients. Elevated circERBIN promoted G1/S transition of HCC cells, thus facilitating the proliferation and tumorigenesis of HCC cells. Mechanistic investigations revealed that circERBIN regulated HCC proliferation by acting as a sponge of miR-1263, which subsequently targeted cyclin dependent kinase 6 and controlled G1/S transition. Conclusion Taken together, these results determined that circERBIN functions as an important epigenetic regulator in HCC development, highlighting that circERBIN is a promising target for treatment of HCC.